Autotaxin–lysophosphatidic acid–LPA3 signaling at the embryo‐epithelial boundary controls decidualization pathways. (6th June 2017) - Aikawa, Shizu; Kano, Kuniyuki; Inoue, Asuka; Wang, Jiao; Saigusa, Daisuke; Nagamatsu, Takeshi; Hirota, Yasushi; Fujii, Tomoyuki; Tsuchiya, Soken; Taketomi, Yoshitaka; Sugimoto, Yukihiko; Murakami, Makoto; et al.
Abstract: During pregnancy, up‐regulation of heparin‐binding (HB‐) EGF and cyclooxygenase‐2 (COX‐2) in the uterine epithelium contributes to decidualization, a series of uterine morphological changes required for placental formation and fetal development. Here, we report a key role for the lipid mediator lysophosphatidic acid (LPA) in decidualization, acting through its G‐protein‐coupled receptor LPA3 in the uterine epithelium. Knockout of Lpar3 or inhibition of the LPA‐producing enzyme autotaxin (ATX) in pregnant mice leads to HB‐EGF and COX‐2 down‐regulation near embryos and attenuates decidual reactions. Conversely, selective pharmacological activation of LPA3 induces decidualization via up‐regulation of HB‐EGF and COX‐2. ATX and its substrate lysophosphatidylcholine can be detected in the uterine epithelium and in pre‐implantation‐stage embryos, respectively. Our results indicate that ATX–LPA–LPA3 signaling at the embryo‐epithelial boundary induces decidualization via the canonical HB‐EGF and COX‐2 pathways. Synopsis: The signaling cascade leading to embryo implantation in the uterus and the accompanying morphological and physiological changes, termed decidualization, are controlled by the lysophosphatidic acid (LPA) receptor LPA3, which is activated by epithelial autotaxin‐dependent LPA synthesis from an embryo‐derived precursor. LPA3 activation induces decidualization, characterized by extensive uterine proliferation and angiogenesis. HB‐EGF and COX‐2 induction upon selective LPA3 stimulation promotes Bmp2/Wnt4 expression in the uterine epithelium. Pharmacological inhibition of HB‐EGF, COX‐2 or Bmp2/Wnt4 signaling suppresses decidualization induced by LPA3 agonists. LPA3 activation in the vicinity of the embryo depends on the LPA‐producing enzyme autotaxin in pregnant mice. Detection of the autotaxin substrate lysophosphatidylcholine in embryos suggests the LPA precursor is provided selectively at the implantation stage. Abstract : Interaction of preimplantation embryo and uterine epithelium facilitates synthesis of lysophosphatidic acid, which triggers HB‐EGF and SOX‐2 signal required for implantation in the uterus.